A randomised clinical trial to evaluate the effect of a 67 % sodium bicarbonate-containing dentifrice on 0.2 % chlorhexidine digluconate mouthwash tooth staining. Issue 1 (December 2016) - Akwagyiram, Ivy; Butler, Andrew; Maclure, Robert; Colgan, Patrick; Yan, Nicole; Bosma, Mary
Abstract Background Gingivitis can develop as a reaction to dental plaque. It can be limited by curtailing plaque build-up through actions including tooth brushing and the use of medicinal mouthwashes, such as those containing chlorhexidine digluconate (CHX), that can reach parts of the mouth that may be missed when brushing. This study aimed to compare dental stain control of twice-daily brushing with a sodium fluoride (NaF) dentifrice containing 67 % sodium bicarbonate (NaHCO3 ) or a commercially available NaF silica dentifrice without NaHCO3, while using a mouthwash containing 0.2 % CHX. Methods This was a 6-week, randomised, two-site, examiner-blind, parallel-group study in healthy subjects with at least 'mild' stain levels on the facial surfaces of ≥4 teeth and ≥15 bleeding sites. Assessment was via modified Lobene Stain Index (MLSI), the score being the mean of stain intensity multiplied by area (MLSI [IxA]). Results One hundred and fifty of 160 randomised subjects completed the study. There were no significant differences in Overall (facial and lingual) MLSI (IxA) scores between dentifrices. The Facial MLSI (IxA) was statistically significant at 6 weeks, favouring the 67 % NaHCO3 dentifrice (p  = 0.0404). Post-hoc analysis, conducted due to a significant site interaction, found significant differences for all MLSI scores in favour of the 67 % NaHCO3 dentifrice at Site 1 (both weeks) but not Site 2. Conclusions No overall significant differences were found between a 67 and 0 % NaHCO3 dentifrice in controlling CHX stain; a significant difference on facial surfaces suggests advantage of the former on more accessible surfaces. Trial registration This study was registered at ClinicalTrials.gov (NCT01962493 ) on 10 October 2013 and was funded by GSK Consumer Healthcare.